Hubungan Kecerdasan Emosional Dengan Keyakinan Diri Mahasiswa Dalam Belajar Praktik Tari Gunungsari Gaya Surakarta - Maulina, Alfiah (Jurnal Pendidikan Tari, 2021)
This study aims to describe the relationship between emotional intelligence and self-efficacy in Students in Learning Surakarta Style Gunungsari Dance Practice at Students of the Dance Education Study Program, Faculty of Language and Arts, State University of Jakarta. This study used survey quantitative research method. The results The results of the study are as follows: 1) There is no relationship between emotional intelligence and self-confidence in learning the Surakarta style Gunungsari dance practice with a correlation coefficient of 0.251 with a low degree of correlation; 2) the value of is 0.063 or 6.3%; 3) sig value 0.166> 0.05; 4) value is 1.421 <t table 2.042. it can be concluded that the variable (X) emotional intelligence has no effect on self-confidence (Y), because it only gives a significance of 6.3%. While the remaining 93.7% is influenced by other factors outside the emotional intelligence variable. The results of this study were obtained with the conditions of online learning during the COVID-19 pandemic. So it can be concluded that the hypothesis is rejected.